Dietary Fiber in Health and Disease - Dreher, Mark L. (Nutrition and Health, 2018)
This newest addition to the Nutrition and Health series is a comprehensive, yet portable, guide to the use of dietary fiber for the management of health and disease. Dietary Fiber in Health and Disease covers all sources of dietary fiber with a focus on preventing and managing chronic diseases. Each chapter contains a careful analysis with many figures and tables of the most recent human dietary fiber studies and includes specific recommendations on the fiber types and intake levels required to prevent and manage chronic disease and improve health. Additionally, physicians, dietitians, nurses, nutritionists, pharmacists, food industry scientists, academic researchers and educators, naturopathic doctors, and other health professionals will be drawn to the practical, ready-to-use information and coverage of subjects such as fiber in gastrointestinal health and disease, fiber in cancer prevention, fiber in Type 2 Diabetes, and fiber in body weight and composition. Dietary Fiber in Health and Disease will be of interest to physicians and other healthcare professionals in many different specialties, including general practitioners, oncologists, endocrinologists, and other practitioners looking to implement dietary advice as part of the patient treatment plan.